2022
DOI: 10.1111/febs.16321
|View full text |Cite
|
Sign up to set email alerts
|

Double stranded DNA breaks and genome editing trigger loss of ribosomal protein RPS27A

Abstract: DNA damage activates a robust transcriptional stress response, but much less is known about how DNA damage impacts translation. The advent of genome editing with Cas9 has intensified interest in understanding cellular responses to DNA damage. Here, we find that DNA double-strand breaks (DSBs), including those induced by Cas9, trigger the loss of ribosomal protein RPS27A from ribosomes via p53-independent proteasomal degradation. Comparisons of Cas9 and dCas9 ribosome profiling and mRNA-seq experiments reveal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Ribosomal proteins are important for the assembly of ribosomal subunits and also function as RNA chaperones (X. Xu, Xiong, and Sun 2016). The specific down regulation of ribosomal genes observed here suggests that there a may be a global inhibition of protein translation in response to DNA damage as has been reported following a CRISPR-Cas9 induced DSB in mammalian cells (Riepe et al 2021).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Ribosomal proteins are important for the assembly of ribosomal subunits and also function as RNA chaperones (X. Xu, Xiong, and Sun 2016). The specific down regulation of ribosomal genes observed here suggests that there a may be a global inhibition of protein translation in response to DNA damage as has been reported following a CRISPR-Cas9 induced DSB in mammalian cells (Riepe et al 2021).…”
Section: Resultssupporting
confidence: 70%
“…While the purpose of this study was to determine the specific phosphorylation events that govern the DDR in T. brucei, analysis of the proteome revealed that ribosomal proteins are down regulated following a DNA break. A similar phenomenon is seen in human cells where phosphorylation of eIF2a halts translation following a DSBs via ribosome remodelling (Riepe et al 2021), whilst mouse embryonic fibroblasts exposed to global DNA damage results in transcriptional silencing in the nucleolus (Kruhlak et al 2007).…”
Section: Discussionmentioning
confidence: 66%
“…The exact reason is not clear and beyond the scope of this study but may be related to the cellular response following induction of dsDNA breaks. 42 Then we investigated whether the Cas9 dosage titration can improve the GFP transfection efficiency while maintaining a relatively robust TCR KO efficiency (Figure S6D). Our result showed that a reduction of Cas9 to 35 and 17.5 pmol during a single nucleofection enhanced the total GFP+ population to $60% (Figure S6D The second strategy was based on sequential delivery of CRISPR-Cas9 RNP and pmaxGFP (24 h later) to generate GFP+TCR/CD3 neg T cells (Figure S5A, middle).…”
Section: Non-viral Transfection Of a Transgene Of Interest In The Tcr...mentioning
confidence: 99%
“…If this were the case, it would not be the first occurrence of a direct link between translation and DNA repair. A recent study reports that DNA double strand breaks can trigger the proteasomal degradation of a specific ribosomal protein in eukaryotes, with a direct impact on ribosome composition (66). Translational reprogramming in response to DNA damage can thus be an advantageous property selected during evolution.…”
Section: Discussionmentioning
confidence: 99%